Experiences with the OECD 308 transformation test: A human pharmaceutical perspective. (21st November 2013) - Ericson, Jon F; Smith, Richard Murray; Roberts, Gary; Hannah, Bob; Hoeger, Birgit; Ryan, Jim
ABSTRACT The Organisation for Economic Co‐operation and Development (OECD) 308 water–sediment transformation test has been routinely conducted in Phase II Tier A testing of the environmental risk assessment (ERA) for all human pharmaceutical marketing authorization applications in Europe, since finalization of Environmental Medicines Agency (EMA) ERA guidance in June 2006. In addition to the "Ready Biodegradation" test, it is the only transformation test for the aquatic/sediment compartment that supports the classification of the drug substance for its potential persistence in the environment and characterizes the fate of the test material in a water–sediment environment. Presented is an overview of 31 OECD 308 studies conducted by 4 companies with a focus on how pharmaceuticals behave in these water–sediment systems. The geometric mean (gm) parent total system half‐life for the 31 pharmaceuticals was 30 days with 10th/90th percentile (10/90%ile) of 14.0/121.6 d respectively, with cationic substances having a half‐life approximately 2 times that of neutral and anionic substances. The formation of nonextractable residues (NER) was considerable, with gm (10/90%ile) of 38% (20.5/81.4) of the applied radioactivity: cationic substances 50.8% (27.7/87.6), neutral substances 31.9% (15.3/52.3), and anionic substances 16.7% (9.5/30.6). In general, cationic substances had fewer transformation products and more unchanged parent remaining at day 100 of the study. A review of whether a simplified 1‐point analysis could reasonably estimate the parent total system half‐life showed that the total amount of parent remaining in the water and sediment extracts at day 100 followed first‐order kinetics and that the theoretical half‐life and the measured total system half‐life values agreed to within a factor of 1.68. Recommendations from this 4‐company collaboration addressed: 1) the need to develop a more relevant water–sediment transformation test reflecting the conditions of the discharge scenario more representative of human pharmaceuticals, 2) potential use of a 1‐point estimate of parent total system half‐life in the EMA ERA screening phase of testing, 3) the need for a more consistent and transparent interpretation of the results from the transformation study; consistent use of terminology such as dissipation, transformation, depletion, and degradation in describing their respective processes in the ERA, 4) use of the parent total system dissipation half‐life in hazard classification schemes and in revising predicted environmental concentration in ERA, and 5) further research into cationic pharmaceuticals to assess whether their classification as such serves as a structural alert to high levels of NER; and whether this results in reduced bioavailability of those residues. Integr Environ Assess Manag 2013;X:000–000. © 2013 SETAC Integr Environ Assess Manag 2014;10:114–124. © 2013 SETAC